2020
DOI: 10.1186/s42269-020-00440-7
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the FINDRISC tool in predicting the risk of developing type 2 diabetes mellitus in a young adult Nigerian population

Abstract: Background The global prevalence of diabetes mellitus is assuming worrisome proportions even among children and young adults. This study is aimed at predicting the risk of developing type 2 diabetes mellitus in a young adult Nigerian population using the validated FINDRISC tool. Results Data on 134 young adults [67 (50.0%) male and 67 (50.0%) female] analyzed in this study revealed a body mass index value of 24.86 ± 3.38 kg/m2 (male) and 25.42 ± 5.39 kg/m2 (female) with 43.2% of participants being overweigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 26 publications
1
3
0
1
Order By: Relevance
“…This study result is significantly similar to a study in Abuja, Nigeria, by Nnamudi et al 15 , with the female participants having higher mean values of BMI (25.4 ± 5.4 vs 24.9 ± 3.4) and high mean FINDRISC score (7.3 ± 3.4 vs 4.9 ± 3.2) relative to the males. Another study in India showed that urban women in India displayed higher levels of overweight and obesity due to unfavorable diets and lower physical activity levels when compared to rural women 43 .…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…This study result is significantly similar to a study in Abuja, Nigeria, by Nnamudi et al 15 , with the female participants having higher mean values of BMI (25.4 ± 5.4 vs 24.9 ± 3.4) and high mean FINDRISC score (7.3 ± 3.4 vs 4.9 ± 3.2) relative to the males. Another study in India showed that urban women in India displayed higher levels of overweight and obesity due to unfavorable diets and lower physical activity levels when compared to rural women 43 .…”
Section: Discussionsupporting
confidence: 90%
“…Similar to this study in Nigeria, the FINDRISC questionnaire also observed a significantly high Body Mass Index (BMI) in the population residing in urban and semi-urban communities in Nigeria. For example, Nnamudi et al 15 found that 43.2% of Asaba, Delta State study participants were overweight or obese. Likewise, Agu et al 42 noticed that 42.6% of the study population in Onitsha, Anambra State were obese.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 1 , 2 It suffices to state that the prevalence of diabetes, diabetes-related deaths, and global healthcare expenditures on T2DM continue to rise globally, 3 thus making diabetes a primary global health concern, especially in the developing and underdeveloped nations of the world. 4 Besides, standard diagnostic tests, such as the glycated hemoglobin (HbA1c) and the Oral Glucose Tolerance Test (OGTT), are expensive and difficult to scale up in a large population, 5 especially in resource-limited countries such as Vietnam. Moreover, timely screening for identifying individuals with undiagnosed T2DM is the key to diagnosing diabetes at the early stages and preventing T2DM complications.…”
Section: Introductionmentioning
confidence: 99%
“…Bu sonuçlar istatistiksel olarak anlamlı idi (Tablo 3). Literatürde çalışmamızla benzer sonuçları içeren araştırmalar olduğu gibi(11,17,19) farklı sonuçları içeren çalışmalarda bulunmaktadır(20)(21).Bu araştırmada taramaya katılan bireylerin %37,9' unun birinci derece akrabalarında,…”
unclassified